TERAPI HOLISTIK DALAM PERAN YESUS SEBAGAI TABIB KARISMATIK - Nur Fitriyana (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2018)
Jesus was understood as an ordinary human being at his first appeareance, then he appeared as a rabbi, messiah and prophet, and performed his role not only as a charismatic rabbi or a prophet, but also a charismatic physician. Jesus implements loving others, by healing sick people in a different way from the practices that occur in their society. He is not a medical expert and not a professional doctor. Although in his day there were many doctors and physicians, but the amount was little and their knowledge about medicine was very limited. Moreover, poor people are rarely able to pay them. Besides that there are also professional exorcists who are able to expel evil spirits by using ancient ceremonial formulas in the form of incantations, symbolic actions, certain items and mention of someone's name. Sometimes saints also appear who are able to bring rain and heal with simple and spontaneous prayer to God. It seems that Jesus is using a different therapy from his day, which is holistic therapy. In the world of medicine, it is known as holistic medicine, which is synergizing the physical, mental, spiritual and emotional elements of a person in maintaining their health.